Model Interaksi Sosial dalam Forum Virtual - Abyan Arrasid; Anne Maryani (UNISBA Press, 2022)
Abstract. The development and progress of today's technology continues to grow rapidly. Modern technology allows users to fulfill their social needs without meeting face to face. Without realizing it, the human community has emerged in two worlds, namely real life and virtual life (cyber community). This study aims to determine how the model of social interaction in a virtual community on the Discord Channel